Modulating Effects of Diets High in ω‐3 and ω‐6 Fatty Acids in Initiation and Postinitiation Stages of Diethylnitrosamine‐induced Hepatocarcinogenesis in Rats - Rahman, K. M. Wahidur (Jpn J Cancer Res, 1999)
The effects of sardine fish oil or corn oil on diethylnitrosamine (DEN)‐induced hepatocarcinogenesis were investigated in male F344 rats. Starting at 5 weeks of age, animals were divided into 11 groups and fed 23.5% corn oil (HCO) (groups 1 and 7) or 5% corn oil (LCO) (groups 2 and 8), 22.5% sardine oil + 1% corn oil (FO) semipurified diet (groups 3 and 9) or basal diet (CE‐2) (groups 4–6, 10 and 11). At 6 weeks of age, all animals except the vehicle‐treated groups were given DEN (200 mg/kg body weight, i.p. once weekly for 3 weeks). One week after the final exposure to DEN, groups 1–3 were changed to the basal diet, and groups 4–6 were switched to the HCO, LCO or FO diet, respectively. Animals in groups 1–3 and 10 were given drinking water containing 0.05% phenobarbital (PB). Liver sections from the animals at the termination of the experiment (24 weeks) were doubly stained for glutathione S‐transferase placental form (GST‐P) and silver‐stained nucleolar organizer regions (AgNORs). The multiplicity of hepatocellular neoplasms of group 1 was significantly larger than that of group 2 or 3. The number of GST‐P‐positive foci of group 2 or 3 was significantly smaller than that of group 1. Among the groups fed the experimental diets in the post initiation phase (groups 4–6), no significant difference was found in the incidence of liver tumors. AgNORs values of the enzyme‐altered foci in rats of the HCO diet groups were larger than those of the other diet groups. These results indicate that the enhancing effect of a high dose of corn oil in hepatocarcinogenesis is mainly present during the initiation phase but not during post initiation phase, and fish oil rich in polyunsaturated ω‐3 fatty acids could inhibit DEN‐induced hepatocarcinogenesis in rats.